The Effect of Microfinance on Entrepreneurship Development in Rolpa District, Nepal (OCEM Journal of Management, Technology & Social Sciences, 2024)
The main objective of this study was to evaluate the effect of microfinance in entrepreneurship development. This study guided from the descriptive and casual comparative research design and it is based on deductive research approach. For this study, non-probability convenience sampling method was applied to collect four hundred survey data from the small entrepreneurs as well as the clients of microfinance intuitions in Rolpa District of Nepal. The five point Likert type scale data was consisted from primary sources. The descriptive analysis is investigated using central tendency of variables and Pearson Correlation was also applied. Multiple Linear Regression Models were used to examine the effect of microfinance on entrepreneurship development. The result showed that 60.30 percent of the variation in dependent variable is explained by independent variables.The results suggested that all the independent variables contributed to the creation of entrepreneurship development and also played a significant role in the entrepreneurship development of small entrepreneurs. Further, the result indicated that there is a positive relationship between all independent and dependent variables. The results also found that lending services, training and education services, barriers and financial resources have positive and statistically significant impact on success of entrepreneurship development. But, saving services have insignificant positive impact on success of entrepreneurship development. Therefore, the study reveals that microfinance is the effective instrument and contributes significant role for the growth and success of small entrepreneurship. It also helps policy makers, microfinance institutions, and small entrepreneurs for new insights to improve the entrepreneurship development and take right decision on microfinance related activities in Nepal.